2016
DOI: 10.1530/rep-16-0074
|View full text |Cite
|
Sign up to set email alerts
|

Spatial differences in gene expression in the bovine oviduct

Abstract: The aim of this study was to compare the transcriptome of the oviductal isthmus of pregnant heifers with that of cyclic heifers as well as to investigate spatial differences between the transcriptome of the isthmus and ampulla of the oviduct in pregnant heifers. After synchronizing crossbred beef heifers, those in standing oestrus (=Day 0) were randomly assigned to cyclic (non-bred, n = 6) or pregnant (artificially inseminated, n = 11) groups. They were slaughtered on Day 3 and both oviducts from each animal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 65 publications
(67 reference statements)
5
38
0
Order By: Relevance
“…Interestingly, gene expression studies of the oviduct in which the early embryo develops show little change due to the presence of an embryo following transfer in the absence of SP (Maillo et al 2015). In fact, further studies reveal that gene expression in the oviduct isthmus following AI is unchanged by the presence of an embryo when compared with oviductal cells at estrus (Maillo et al 2016). The authors conclude from these studies that gene expression in the oviduct, and subsequent production of embryokines, is dependent only on estrous cycle stage.…”
Section: Current Reproductive Strategies In Domestic Species and The mentioning
confidence: 88%
“…Interestingly, gene expression studies of the oviduct in which the early embryo develops show little change due to the presence of an embryo following transfer in the absence of SP (Maillo et al 2015). In fact, further studies reveal that gene expression in the oviduct isthmus following AI is unchanged by the presence of an embryo when compared with oviductal cells at estrus (Maillo et al 2016). The authors conclude from these studies that gene expression in the oviduct, and subsequent production of embryokines, is dependent only on estrous cycle stage.…”
Section: Current Reproductive Strategies In Domestic Species and The mentioning
confidence: 88%
“…After flushing, each section of the oviduct was opened longitudinally and gently scraped with a blade to recover the epithelial cells. The same procedure has been previously performed by us (Maillo et al, ) in which the epithelial nature of the recovered cells was confirmed by ‘flow cytometry analysis’ using antibodies anti‐bovine‐pancadherin (C1821), anti‐bovine‐pancytokeratin (C2931) and anti‐bovine‐vimentin (V2258). The cells obtained after centrifugation (18.8 g for 1 min at 4°C) were snap‐frozen and stored at −80°C until gene expression analysis.…”
Section: Methodsmentioning
confidence: 91%
“…Sample recovery on Day 2.5 was performed in order to be certain that (a) the embryo would be found within the oviduct and (b) that the embryo location enabled the collection of the oviductal portions surrounding the embryo section (i.e., proximal and distal sections). However, as described, this early embryo recovery entailed finding the embryos around the ampullary–isthmic junction, which may mask the embryo effect due to the spatial differences in gene expression between the two sections of the oviduct (Maillo et al, ). In line with this, the fact that three out of the four embryos recovered at Day 2.5 were at the 2‐cell stage—that is before major embryo genome activation, which in cattle occurs around the 8‐cell stage (Graf et al, )—could have influenced the oviduct response, which in vitro has been demonstrated to be embryo stage‐specific (Hamdi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The oviduct is a dynamic organ comprising different anatomical and functional regions that may show differences in mRNA expression levels and in the synthesis and secretion of various proteins (Maillo et al, 2016). Thus, the present study focuses on the expression of MMP2, MMP9, TIMP1 and TIMP2 in the llama oviductal segments and the active and inactive MMP forms present in the OF.…”
Section: Discussionmentioning
confidence: 99%